PADATAN TERSUSPENSI DI MUARA SUNGAI ROKAN KABUPATEN ROKAN HILIR PROVINSI RIAU - Metry, Gita; Ghalib, Musrifin; ', Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on October 2016 at Estuary of Rokan River Rokan Hilir Regency Riau Province. This study aimed to find out how big suspended solid in Estuary of Rokan River. The method used survey and purposive sampling. Results showed the suspended solid on base from 60 mg/l for station 5,6,11 and 520 mg/l for station 4. Showed the suspended solid on surface from 50 mg/l for station 3,6,11 and110 mg/l for station 10. Based on data obtained, it can be concluded that total suspended solid present in the Estuary of Rokan River is high. Keywords: Suspended Solid, Estuary of Rokan River, and Station